## Rotating Magnetic Field

• When three phase supply is given to three phase winding, it produces rotating magnetic field which rotates and synchronous speed.
• Similarly, when two phase supply is given to the two-phase winding, the rotating magnetic field produced by the winding is given here.

### Rotating Magnetic Field: Two Phase Winding

• Let us consider that the two windings P and Q are placed at 90o with respect to each other.
• We assume that when the two phase supply is given to the winding, flux produces in each winding is purely sinusoidal.
• The waveform of the flux is shown in the figure B.
• The direction of the flux is assumed as positive whereas its opposite sides indicate negative values. The instantaneous value of flux can be given by

FP = Fm Sin θ

FQ = Fm Sin ( θ – 90o )

• The voltage of the winding P is taken as reference or zero degree and winding Q is taken at 90 degree with respect to winding P.

Rotating Magnetic Field: Point 1

The voltage of winding P is zero whereas winding Q is negative as shown in the figure. The voltage of the winding Q negative sign is taken because we assume that the direction of voltage for winding P and winding Q is positive in the first quadrant.

FP = 0 and

FQ = –  Fm

Resultant flux F = √ P2 + Q2 – 2PQCos θ

= √ 0 + ( –  Fm )2 – 0

=  Fm

Rotating Magnetic Field: Point 2

The voltage of the winding P and winding Q is 45 degrees but both are in the opposite direction.

FP = Fm / √ 2 and

FQ = –  Fm / √ 2

Resultant flux F = √ P2 + Q2 – 2PQCos θ

= √ Fm2 / 2 + Fm2 / 2 + 0

=  Fm

Rotating Magnetic Field: Point 3

The voltage of the winding P is at 90 degree but voltage of the winding Q is at and winding Q is 180 degree.

FPFm and

FQ = 0

Resultant flux F = √ P2 + Q2 – 2PQCos θ

= √ ( Fm )2 + 0

=  Fm

Rotating Magnetic Field: Point 4

The voltage of the winding P is at 135 degree but voltage of the winding Q is at and winding Q is 45 degree but both are in the opposite direction.

FP = – Fm / √ 2 and

FQ = Fm / √ 2

Resultant flux F = √ P2 + Q2 – 2PQCos θ

= √ Fm2 / 2 + Fm2 / 2 + 0

=  Fm

#### 1 comment:

1. This comment has been removed by the author.